Regional base composition variation along yeast chromosome III: evoluation of chormosome primary structure - Paul M. Sharp; Andrew T. Lloyd (1993)
Journal Article Regional base composition variation along yeast chromosome III: evoluation of chormosome primary structure Get access Paul M. Sharp, Paul M. Sharp Department of Genetics, Trinity CollegeDublin 2, Ireland Search for other works by this author on: Oxford Academic PubMed Google Scholar Andrew T. Lloyd Andrew T. Lloyd Department of Genetics, Trinity CollegeDublin 2, Ireland Search for other works by this author on: Oxford Academic PubMed Google Scholar Nucleic Acids Research, Volume 21, Issue 2, 25 January 1993, Pages 179–183, https://doi.org/10.1093/nar/21.2.179 Published: 25 January 1993 Article history Received: 25 November 1992 Revision received: 14 December 1992 Accepted: 14 December 1992 Published: 25 January 1993